Whose line is it anyway: graphic anthology drawing the line as a counter to mainstream rape reportage in India. Issue 5 (3rd September 2022) - Yadav, N.
ABSTRACT: Published by Delhi's feminist press Zubaan Book and Toronto's Ad Astra Comix, Drawing the Line: Indian Women Fight Back is an anthology of graphic narratives by fourteen young women. The book came into being as a result of a workshop held in the wake of the brutal gang rape and murder of a young female medical student in Delhi in December 2012; the incident received extensive national and international media coverage and triggered massive civic protests across the country. The ensuing national conversation around rape was shaped in a significant manner by media reportage which ranged from fact-based reports of the night's events to impassioned opinion pieces. However, as scholars like Deepa Fadnis and Shakuntala Rao have pointed out, the newsgathering and reporting process is heavily influenced by patriarchal socialisation; as a result, the conversation rarely moves beyond the language of surveillance and control of female bodies under the rhetoric of women's safety. An anthology like Drawing the Line, I argue, offers a valuable counter-narrative to the problematic public discussion around rape. The anthology explores, in the black-and-white of newsprint and documentary photojournalism, a gamut of issues that undergird rape culture; these include punitive beauty standards, enforced heteronormativity, restrictions on mobility, lack of economic independence, street harassment etc. Equally importantly, the stories articulate a desire for what Shilpa Phadke calls the right to risk and pleasure. My paper, therefore, will explore this graphic anthology as an image-text archive that resists the hegemony of the mainstream discourse by significantly broadening its concerns and offering perspectives that interrogate the status quo's espousal of the rhetoric of safety.